PENGARUH PENGGUNAAN WEBSITE SEKOLAH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI TKJ DI SMK NEGERI 1 KENDIT - Astindari, Tri; Ida Fitriana Ambarsari; Nur Hasanah; Aenor Rofek; Anis Febriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to investigate the effect of using a school website on the Mathematics learning outcomes of class XI TKJ 2 students on two-variable equations and inequalities at SMK Negeri 1 Kendit using quantitative research methods. The respondents in this study were class XI TKJ 2 students who used the school website as a learning resource. The research instrument used was a questionnaire distributed to students to measure the frequency of use of the school website and daily mathematics test scores for two-variable equations and inequalities. The data analysis technique used is simple linear regression to identify the influence between the independent variable (use of the school website) and the dependent variable (Mathematics learning outcomes). The results of the research can be concluded that the simple linear regression equation obtained a constant value of 74.822. The coefficient for the independent variable (x) using the school website which is listed as active is positive, indicating that there is a unidirectional relationship or between the use of the school website (x) and learning outcomes (y). The variable regression coefficient (x) of 3.479 means that every use of the school website (x) by one unit will cause an increase in learning outcomes (y) by 3.479 and is confirmed by a significance value of 0.003 where this value is smaller than the real level (α) 0.05, this means that (Ho) is rejected and (H1) is accepted, so it can be concluded that there is an influence of using the school website on the mathematics learning outcomes of Class XI TKJ students at SMK Negeri 1 Kendit.